Aquaglyceroporins: Generalized metalloid channels - Mukhopadhyay, Rita; Bhattacharjee, Hiranmoy; Rosen, Barry P. (Biochimica et biophysica acta, 2014)
Aquaporins (AQPs), members of a superfamily of transmembrane channel proteins, are ubiquitous in all domains of life. They fall into a number of branches that can be functionally categorized into two major sub-groups: i) orthodox aquaporins, which are water-specific channels, and ii) aquaglyceroporins, which allow the transport of water, non-polar solutes, such as urea or glycerol, the reactive oxygen species hydrogen peroxide, and gases such as ammonia, carbon dioxide and nitric oxide and, as described in this review, metalloids. This review summarizes the key findings that AQP channels conduct bidirectional movement of metalloids into and out of cells. As(OH)3 and Sb(OH)3 behave as inorganic molecular mimics of glycerol, a property that allows their passage through AQP channels. Plant AQPs also allow the passage of boron and silicon as their hydroxyacids, boric acid (B(OH)3) and orthosilicic acid (Si(OH)4), respectively. Genetic analysis suggests that germanic acid (GeO2) is also a substrate. While As(III), Sb(III) and Ge(IV) are toxic metalloids, borate (B(III)) and silicate (Si(IV)) are essential elements in higher plants. The uptake of environmental metalloids by aquaporins provides an understanding of (i) how toxic elements such as arsenic enter the food chain; (ii) the delivery of arsenic and antimony containing drugs in the treatment of certain forms of leukemia and chemotherapy of diseases caused by pathogenic protozoa; and (iii) the possibility that food plants such as rice could be made safer by genetically modifying them to exclude arsenic while still accumulating boron and silicon. This article is part of a Special Issue entitled Aquaporins. •Aquaporins (AQPs) are metalloid channels ubiquitous in all domains of life.•AQPs conduct boron, germanium, silicon, arsenic, and antimony bidirectionally.•As(III), Sb(III) and Ge(IV) are toxic metalloids, and uptake is adventitious.•B(III) and Si(IV) are nontoxic plant growth enhancers under conditions of stress.•Arsenic/antimony compounds are drugs for antimicrobial and anticancer chemotherapy.